The Qur'anic Value of Maryam 'Alaihassalam's Story as an Inspiration for Handling Baby Blues and Strengthening the Resilience of Muslim Families - Erman Gani; Nabil Makarim (MUI Kota Pekanbaru, 2025)
Baby blues syndrome is an emotional condition commonly experienced by mothers after childbirth as a result of hormonal changes, psychological pressure, and the demands of assuming a new maternal role. Although temporary in nature, baby blues can affect marital harmony and family resilience if not addressed appropriately. This article aims to examine the phenomenon of baby blues from a Qur'anic perspective through a reflection on the story of Maryam ('alaihassalam), and to explore relevant Qur'anic values as inspiration for managing baby blues and strengthening Muslim family resilience. This study employs a library research method with a descriptive-analytical approach, examining Qur'anic verses, classical and contemporary tafsir, as well as psychological literature related to maternal mental health in the postpartum period. The findings indicate that the story of Maryam portrays immense emotional pressure, including profound sadness and a desire to withdraw or disappear, which psychologically resembles the symptoms of baby blues. However, the Qur'an also presents forms of divine intervention in the form of spiritual support, inner tranquility, and the fulfillment of physical needs, which become key elements in Maryam's recovery. Values such as patience, faith, empathy, and the importance of social support—particularly the role of the husband as qawwam—serve as fundamental principles in building a sakinah, mawaddah, wa rahmah family. Thus, the story of Maryam not only serves as a spiritual exemplar but also offers a holistic approach to managing baby blues that is relevant to modern Muslim families.